2014
DOI: 10.1039/c4dt02007c
|View full text |Cite
|
Sign up to set email alerts
|

Selective complexation of α-amino acids and simple peptides via their carboxylate groups

Abstract: The complexation of anions of selected α-amino acids (alanine, valine, proline, tyrosine) and small peptides (L-alanyl-L-alanine, L-alanyl-L-alanyl-L-alanine, and L-alanyl-L-alanyl-L-alanyl-L-alanine) by the dinuclear nickel(II) complex [LNi2(μ-Cl)]+ (1), where (L)2− represents a 24-membered binucleating hexamine-dithiophenolato ligand, has been investigated. The following complexes were prepared, isolated as perchlorate or tetraphenylborate salts, and characterized by UV/Vis, IR, and CD spectroscopy: [LNi2(μ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The UV–vis spectrum of apo-DddK in the presence of Ni­(II) shows weak absorption bands at 375 nm (272 M –1 cm –1 ), 610 nm (72 M –1 cm –1 ), 945 nm (102 M –1 cm –1 ), and 1020 nm (105 M –1 cm –1 ), indicating the formation of a Ni­(II) complex with an octahedral coordination (Figure S6). A shoulder near 300 nm (∼860 M –1 cm –1 ) was observed that can be attributed to tyrosinate-Ni­(II) interaction, given a Ni­(II)-phenolate chromophore has been shown to exhibit bands between 200 and 400 nm and a Ni­(II)-thiolate species has an absorption feature at 315 nm. , In contrast, intense LMCT transitions due to Ni­(II)-phenolate that appear between 400 and 600 nm (ε > 900 M –1 cm –1 ) , were not present. Interestingly, in the diacrylate-bound Ni­(II)-DddK structure, Tyr 64 does not participate as a metal ligand (Figure D).…”
Section: Resultsmentioning
confidence: 97%
“…The UV–vis spectrum of apo-DddK in the presence of Ni­(II) shows weak absorption bands at 375 nm (272 M –1 cm –1 ), 610 nm (72 M –1 cm –1 ), 945 nm (102 M –1 cm –1 ), and 1020 nm (105 M –1 cm –1 ), indicating the formation of a Ni­(II) complex with an octahedral coordination (Figure S6). A shoulder near 300 nm (∼860 M –1 cm –1 ) was observed that can be attributed to tyrosinate-Ni­(II) interaction, given a Ni­(II)-phenolate chromophore has been shown to exhibit bands between 200 and 400 nm and a Ni­(II)-thiolate species has an absorption feature at 315 nm. , In contrast, intense LMCT transitions due to Ni­(II)-phenolate that appear between 400 and 600 nm (ε > 900 M –1 cm –1 ) , were not present. Interestingly, in the diacrylate-bound Ni­(II)-DddK structure, Tyr 64 does not participate as a metal ligand (Figure D).…”
Section: Resultsmentioning
confidence: 97%
“…The doubly deprotonated form, L 2− , is an effective dinucleating ligand that readily forms bioctahedral complexes of the type [M 2 L( μ ‐L′)] + with various first‐row transition metal ions (M=Mn 2+ , Fe 2+ , Co 2+ , Co 3+ , Ni 2+ , Figure 1 ). [38] Several co‐ligands such as L′=Cl − , OH − , [39] HS − , [40] and RCO 2 − ,[ 41 , 42 , 43 , 44 , 45 , 46 ] to name just a few, can be accommodated between the divalent metal ions. Complexes of this kind offer the opportunity to investigate intramolecular magnetic super‐exchange interaction as a function of the electronic configuration of the metal ions and the type of the coligand.…”
Section: Introductionmentioning
confidence: 99%